2020
DOI: 10.1152/ajprenal.00132.2020
|View full text |Cite
|
Sign up to set email alerts
|

MiR-21 promotes calcium oxalate-induced renal tubular cell injury by targeting PPARA

Abstract: Kidney stone disease is a crystal concretion formed in kidneys which has been associated with an increased risk of chronic kidney disease. MicroRNAs are functionally involved in kidney injury. Data mining using a microRNA array database suggested that miR-21 may be associated with calcium oxalate monohydrate (COM)-induced renal tubular cell injury. Here, we confirmed that COM exposure significantly upregulated miR-21 expression, inhibited proliferation, promoted apoptosis and caused lipid accumulation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 42 publications
2
18
0
Order By: Relevance
“…Many previous reports have demonstrated that microRNAs (miRNAs) are greatly involved in tubular cell oxidative stress injury and the pathogenesis of CaOx renal stones. It was reported that miRNAs could increase CaOx-induced kidney tubular cell injury and serve as potential therapeutic targets or biomarkers for renal calculi, including miR-21 and miR-155 [18,19]. Our published paper revealed that the interaction of lncRNA H19 with miR-216b contributed to the development of CaOx nephrocalcinosis-induced oxidative stress and tubular cell injury through the regulation of HMGB1/TLR4/NF-kB signaling pathway [5].…”
Section: Introductionmentioning
confidence: 71%
“…Many previous reports have demonstrated that microRNAs (miRNAs) are greatly involved in tubular cell oxidative stress injury and the pathogenesis of CaOx renal stones. It was reported that miRNAs could increase CaOx-induced kidney tubular cell injury and serve as potential therapeutic targets or biomarkers for renal calculi, including miR-21 and miR-155 [18,19]. Our published paper revealed that the interaction of lncRNA H19 with miR-216b contributed to the development of CaOx nephrocalcinosis-induced oxidative stress and tubular cell injury through the regulation of HMGB1/TLR4/NF-kB signaling pathway [5].…”
Section: Introductionmentioning
confidence: 71%
“…Nevertheless, whether miR-21 also participates in the metabolic alterations characterizing ccRCC remains incompletely understood and is of particular interest, especially as this miRNA has been previously shown to target PPAR-α, the master regulator of lipid metabolism [15][16][17]. Furthermore, during kidney fibrosis, miR-21 overexpression contributes to fibrosis and epithelial injury by downregulating PPAR-α expression and increasing lipid accumulation [15,[30][31][32]. In this study, based on our cohort of 52 paired ccRCC tumor tissues and matched adjacent non-tumor tissues, we showed the overexpression of miR-21 in ccRCC as well as an inverse correlation between miR-21 and PPAR-α expression.…”
Section: Discussionmentioning
confidence: 99%
“…Screening for mRNA target prediction identified peroxisome proliferator activated receptor alpha (PPARA) downregulation, an important gene in fatty acid oxidation. This study suggested that miR-21 could potentially be a biomarker for nephrolithiasis and therapeutic target [43]. In a similar study, miR-155 and its role in CaOx-induced renal cell injury was explored by establishing a CaOx-induced HK-2 model that presented cell injury in a dose-dependent manner, increased apoptosis, increased levels of IL1β, IL-6, and TNF-scripta, and elevated expression of miR-155 in treated cells.…”
Section: Dna Expression and Transcriptionmentioning
confidence: 87%